A study on concern about disadvantages online shopping among online shoppers / Noor Syahhirah Ab.Rahim - Ab.Rahim, Noor Syahhirah (2018)
The internet has been develop and improve by year. In Malaysia, internet is one of the phenomena that we can’t prevent it. Same goes to online shopping platform. Online shopping is very convince, variety of items and as shopper there can choose a better price as their budget. There is a lots of advertisement about online shopping in media social. In terms of online buying frequency, according to The Star (Monday, 27 Jun 2016) PwC said although a sizable percentage of consumers in South-East Asia report buying on a daily, weekly, or monthly basis, the percentage was still smaller compared to its overall global survey. It said that 60% of all consumers its global survey reported buying online on a monthly basis or more frequently. This show that online shopper users became higher by year. For online shopper, there will be always the way to find out the best website to buy. Somehow, there will be problem on financial side. Besides, as shopper they put a risk on their product when delivery. However, based on the findings survey by 11street through The Star Media Group on January 2017, 17% of the respondents said they had no shopped online before and 85% is more interest on cash e-commerce services. This is show that not all consumer will use online platform. The researchers will study the advantages and disadvantage of online shopping. How they use online platform as they know. In conclusion, there is always be advantages and disadvantages on how consumers used this platform. Therefore, it is hope that this research will be give more awareness on the online shoppers.